VIRAL DISEASES CHALLENGING THE CANINE AND FELINE FAUNA AND PROSPECTIVE METHODS TO TRACE THEIR ONSET - PANDYA, MAHARSHI; RAVAL, KRUTARTH; RAWTANI, DEEPAK; TYAGI, SANJIV (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Over the last century there has been an alarming increase in the number and diversity of epizootic diseases. Pathogens associated with these diseases may be bacterial, viral or parasitic and can spread by direct contact, food, water and/or environment. Zoonosis can lead to disturbances in the production and trade of animal products. Zoonosis comprise of many newly identified infectious diseases as well as many existing ones ex. Canine distemper virus (CDV). These newly identified and less studied viruses are constantly mutating and is a cause of concern for many virologists and veterinarians. Although, with advancement in science and technology, identification of new or previously unknown viruses has become precise and efficient, however, the need of the hour is to focus on identification of potential pathogenicity of the existing and new viruses for development of cure well in advance, to prevent an onset of endemic or a pandemic like ongoing COVID-19. Furthermore, exercising precautionary measures in addition to development of remedial measures will be like developing a double layered defense system as this will promote healthy practices in handling wild animals, maintaining hygiene in their shelter and routine health checkup of technicians working closely with these animals.